Interaction, Autonomy and Motivation in Teaching Articles under Grammar Tasks - MOUMENE, Ahmed (Journal of Human Sciences, 2009)
This article attempts to compare the effects of two approaches on the teaching of the English definite and indefinite articles: Grammar Consciousness-Raising Tasks and Traditional Grammar. In addition to their avowed beneficial effects on promoting explicit knowledge and grammatical accuracy as indicated in recent literature, the grammar tasks are also found in this research work to improve interaction, autonomy and motivation among students in the classroom.